2020
DOI: 10.3389/fpsyg.2020.01256
|View full text |Cite
|
Sign up to set email alerts
|

Postural Stability and Cognitive Performance of Subjects With Parkinson’s Disease During a Dual-Task in an Upright Stance

Abstract: Background: The reviewed studies on center of pressure (COP) displacement in Parkinson's disease (PD) subjects show important methodological differences and contradictory results with regard to healthy subjects. The dual-task paradigm method has been used to examine cognitive prioritization strategies to control concurrent postural and cognitive tasks. The motor requirements, such as pronouncing words, involved in the cognitive tasks used in double-task conditions could be related to the heterogeneity of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 70 publications
(99 reference statements)
1
15
1
Order By: Relevance
“…This is also demonstrated by the higher level of activation of the prefrontal cortex during walking with increasing age (83). Previous studies also reported higher cognitive DTC in PD (43,84) and stroke patients (4) compared with healthy participants. This has been linked to physical and cognitive impairment related to these disorders and to reduced attention and cognitive reserve (85).…”
Section: E Ect Of Age and Disease Groupmentioning
confidence: 59%
“…This is also demonstrated by the higher level of activation of the prefrontal cortex during walking with increasing age (83). Previous studies also reported higher cognitive DTC in PD (43,84) and stroke patients (4) compared with healthy participants. This has been linked to physical and cognitive impairment related to these disorders and to reduced attention and cognitive reserve (85).…”
Section: E Ect Of Age and Disease Groupmentioning
confidence: 59%
“…In addition, Matinolli et al (2007) demonstrated that individuals with PD who are fallers had higher postural sway and CoP displacement compared to PD non-fallers and healthy controls. Other studies demonstrated increased CoP displacement with visual deprivation and additional cognitive load in individuals with PD ( Marchese et al, 2003 ; Holmes et al, 2010 ; Morenilla et al, 2020 ). In the present study, Figure 2 demonstrated increased CoP displacement in PD fallers with visual occlusion; however, the effect of additional cognitive load was absent measured by CoP displacement.…”
Section: Discussionmentioning
confidence: 83%
“…Each dynamic test will be registered two times. As a result, the primary outcome of the study will be the CoP sway area, which is defined as the surface over which the CoP moves during the measurement and is a valid indicator of detecting postural control changes in dual-task conditions ( Campolettano et al, 2020 ; Morenilla et al, 2020 ). The secondary outcomes are shown in Table 2 and consist of biomechanics and clinical variables related to static and dynamic balance.…”
Section: Materials and Analysismentioning
confidence: 99%